Special Education and Inclusive Practices in the AFAM System: the Opera VR Educational Project in Italian Music Conservatories - Sellari, Giuseppe; Montali, Alessandra (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2025)
The paper offers a reflection on the perspectives of special pedagogy and the evolution of inclusive models within the Higher Education System for Art, Music and Dance (AFAM) in Italy. Starting from an analysis of the theoretical foundations of educational inclusion and the transformative role of special pedagogy, the authors explore how the intersection of the arts, immersive technologies, and pedagogy can create new accessible and meaningful learning environments. Within this framework, the project Opera VR – Virtual Learning and Research Hub, developed as part of the PNRR MTNT initiative, is presented as an immersive and modular environment designed to foster active learning, personalized pathways, and interdisciplinary integration. The project involves a network of Music Conservatories and Fine Arts Academies and is structured around specific learning paths for university students and schoolchildren. Through blended methodologies and inclusive strategies, Opera VR aims to promote artistic, cognitive, and metacognitive skills, in a perspective of empowerment of diversity and transformation of the AFAM educational system. The paper concludes by highlighting the need for an evidence-based approach to fully harness the potential of immersive technologies in support of equitable and personalized education.